2013
DOI: 10.1016/j.alcr.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Ideal ages for family formation among immigrants in Europe

Abstract: This paper investigates ideal ages for marriage and parenthood among immigrants from over 160 countries origins living in 25 European countries. Ideals regarding the timing of family formation are indicative of how individuals perceive the family life course and provide insight into familylife aspirations and the meaning attached to these transitions. Using data from the European Social Survey (Round 3, 2006; N = 6,330) and a cross-classified multilevel modeling approach, we investigate associations between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…Migrants' descendants are subject to the receiving society's institutions and labour markets, which impacts the opportunity structure and thus childbearing. In line with this, it has been shown that across Europe second generation migrants reported higher ideal ages at parenthood than the first generation (Holland and De Valk 2013).…”
supporting
confidence: 67%
“…Migrants' descendants are subject to the receiving society's institutions and labour markets, which impacts the opportunity structure and thus childbearing. In line with this, it has been shown that across Europe second generation migrants reported higher ideal ages at parenthood than the first generation (Holland and De Valk 2013).…”
supporting
confidence: 67%
“…The experience of second-generation Turkish women in Europe may differ from Second-generation Turkish mothers' work 3 that of their majority-group peers, in that their experience of motherhood and its implications for employment while children are young intersect with their position in the socio-cultural middle ground between their parents' country of origin and their own country of birth (Foner 1997;Choo and Ferree 2010;Holland and De Valk 2013).…”
Section: Women and Work Across The Life Coursementioning
confidence: 99%
“…To the extent that gendered norms and values of the first generation persist and influence the values and behaviour of the second generation, we may expect that, on average, the children of Turkish immigrants will hold different preferences from the majority group about the timing of family formation (Holland and De Valk 2013) and different expectations regarding the division of paid and unpaid work and filial responsibilities (Foner 1997;Idema and Phalet 2007). Second-generation Turkish women are more likely to enter a (married) union and have their first child at younger ages than their majority-background counterparts (Huschek et al 2010;Milewski and Hamel 2010).…”
Section: Women and Work Across The Life Coursementioning
confidence: 99%
See 1 more Smart Citation
“…The second generation is born and raised in the host country, but within an immigrant family, which plays an important role in the intergenerational transmission of cultural values (Milewski 2011). Members of the 1.5 generation occupy a "socio-cultural middle ground" (Holland and de Valk 2013) between their countries of origin and destination, and we can presume that their family formation norms and behaviour are shaped by both societal contexts. Previous studies in different contexts, such as Germany (Milewski 2007(Milewski , 2010, Sweden (Scott and Stanfors 2011), the Netherlands (Garssen and Nicholaas 2008), and the United Kingdom (Dubuc 2012), have documented a convergence tendency in the fertility behaviour of immigrant children toward that of natives.…”
Section: Theoretical Framework and Research Questionsmentioning
confidence: 99%